Recent insights about pyrrolidine core skeletons in pharmacology - Poyraz, Samet; Döndaş, H. Ali; Döndaş, Naciye Yaktubay; Sansano, José M. (Frontiers in Pharmacology, 2023)
To overcome numerous health disorders, heterocyclic structures of synthetic or natural origin are utilized, and notably, the emergence of various side effects of existing drugs used for treatment, or the resistance of disease-causing microorganisms renders drugs ineffective.Therefore, the discovery of potential therapeutic agents that utilize different modes of action is of utmost significance to circumvent these constraints. Pyrrolidines, pyrrolidine-alkaloids, and pyrrolidine-based hybrid molecules are present in many natural products and pharmacologically important agents. Their key roles in pharmacotherapy make them a versatile scaffold for designing and developing novel biologically active compounds and drug candidates. This review aims to provide an overview of recent advancements (especially 2015-2023) in the exploration of pyrrolidine derivatives, emphasizing their significance as fundamental components of the skeletal structure. In contrast to previous reviews that have predominantly focused on a singular biological activity associated with these molecules, this review consolidates findings from various investigations encompassing a wide range of important activities (antimicrobial, antiviral, anticancer, anti-inflammatory, anticonvulsant, cholinesterase inhibition, carbonic anhydrase inhibition) exhibited by pyrrolidine derivatives.This study is also anticipated to serve as a valuable resource for drug research and development endeavors, offering significant insights and guidance.